Physiological Response and Tissue Adaptation to Perineal Hernia in Dogs during Surgical and Recovery - Ahmad Syarifuddin Syarif (Journal of Applied Veterinary Science And Technology, 2026)
Background: Recognized as a relatively common surgical condition in geriatric male dogs, particularly intact individuals, perineal hernia occurs due to the weakening or rupture of the pelvic diaphragm muscles. Anatomical failure allows for the protrusion of pelvic or abdominal organs such as the rectum, prostate, or urinary bladder into the perineal region. Improvement of treatment outcomes and recovery, a thorough understanding of the physiological responses and tissue adaptations occurring during and after surgical correction is essential. Purpose: Explored in this case report are the physiological responses and tissue adaptations in a dog diagnosed with a perineal hernia involving the urinary bladder (vesica urinaria), encompassing both pre- and post-surgical periods, while evaluating the effectiveness of the surgical and postoperative management approach. Case(s): A 12 year old intact male dog was presented with progressive perineal swelling and dysuria. Physical examination and rectal palpation identified a unilateral perineal hernia, with the urinary bladder herniated into the perineal region. Case Management: Surgical correction was performed using the internal obturator muscle flap technique. Preoperative stabilization included fluid therapy and analgesia, while postoperative care consisted of antibiotics, pain management, and daily wound care. Monitoring was conducted over four weeks to evaluate tissue adaptation and urinary function recovery. Conclusion: Mild to moderate inflammation was observed during the first postoperative week, followed by granulation tissue formation and progressive strengthening by the third week. Successful recovery indicates that the internal obturator flap technique is effective for repairing perineal hernia involving the urinary bladder.